Occurrence of Fusarium wilt on summer squash caused by Fusarium oxysporum in Assiut, Egypt - Mahmoud, A. F. (Journal of Phytopathology and Disease Management, 2016)
Fusarium wilt of summer squash was first noticed in April and May 2012 in Assiut- Egypt. Symptoms included wilting of the foliage, withering of older leaves and eventually died during growth. The causal pathogen was identified as Fusarium oxysporum Schlecht. Pathogenicity tests of the obtained isolates were demonstrated via artificial inoculation, and it satisfied Koch's postulates. Because summer squash is of great economic importance in Egypt, biological control of the disease was carried out by the biocontrol agent Gliocladium catenulatum. The effect of G. catenulatum against F. oxysporum was investigated in vitro and tested on summer squash plants under greenhouse conditions. G. catenulatum isolates were able to inhibit the growth of F. oxysporum in dual culture. In greenhouse, application of G. catenulatum was tested at three different times. All treatments were effective to reduce disease severity. Application of G. catenulatum preceding the inoculation with F. oxysporum reduced significantly the incidence of Fusarium wilt compared to plants inoculated with F. oxysporum alone. The disease suppression was occurred when G. catenulatum applied five days before infested soil by F. oxysporum. Obtained results indicate that G. catenulatum is very effective biocontrol agents offer potential benefit in Fusarium wilt of squash, and should be harnessed for further biocontrol applications. To our knowledge, this is the first report of F. oxysporum causing wilt of summer squash in Assiut, Egypt.